Answer: The required values are
![f^(-1)(x)=x-4~~~~~~~~\textup{and}~~~~~~~~~f^(-1)(4)=0.](https://img.qammunity.org/2019/formulas/mathematics/high-school/1tecldbt4ifdzo9hi5lzrm8vblt6o1ial3.png)
Step-by-step explanation: We are given the following function f(x) :
![f(x)=x+4~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2019/formulas/mathematics/high-school/g78d4tbfl3tak0lz8ic2otlrnpesglyrv0.png)
We are to find the values of
and
![f^(-1)(4).](https://img.qammunity.org/2019/formulas/mathematics/high-school/s6yedjlz9socq0hria2i6ufsbbo7ei8xtu.png)
Let us consider that
![y=f(x)~~~~~~~~\Rightarrow x=f^(-1)(y).](https://img.qammunity.org/2019/formulas/mathematics/high-school/ulblu4hynhnboze4g20fin2kbx7puoujku.png)
So, from equation (i), we get
![f(x)=x+4\\\\\Rightarrow y=f^(-1)(y)+4\\\\\Rightarrow f^(-1)(y)=y-4\\\\\Rightarrow f^(-1)(x)=x-4.](https://img.qammunity.org/2019/formulas/mathematics/high-school/w36kyy7fkt8e20l7bdix7z02m3pvn2h3xm.png)
Substituting x = 4 in the above equation, we get
![f^(-1)(4)=4-4=0\\\\\Rightarrow f^(-1)(4)=0.](https://img.qammunity.org/2019/formulas/mathematics/high-school/8k5w6iuepxgkq75nun4dz4wexzxl0gp5qf.png)
Thus, the required values are
![f^(-1)(x)=x-4~~~~~~~~\textup{and}~~~~~~~~~f^(-1)(4)=0.](https://img.qammunity.org/2019/formulas/mathematics/high-school/1tecldbt4ifdzo9hi5lzrm8vblt6o1ial3.png)